Georgia Architectural and Historic Properties Survey of Rural [226] South western section of the county, Grooverville, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [226] South western section of the county, Grooverville, Ga. December 1980. Grooverville Methodist. A one story rectangular plan with gabled tin roof and clapboard siding. Sash windows with 9/9 lights and shutters. Brick piers. Square bell towers without spires. Good condition. Date of Construction: c. 1856. According to the History of Brooks County, Ga., this is the oldest church edifice in the county; this makes Grooverville Methodist very significant.
1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.31 MB (1,383,703 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Brooks County (Ga.); Real property surveys; Grooverville, Ga.